The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1088/0953-8984/9/5/013
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Fermi surfaces of coupled double quantum wells in the presence of an in-plane magnetic field

Abstract: The anticrossing of the dispersion relations of two two-dimensional electron gases (2DEGs) in an in-plane magnetic field results in distorted Fermi surfaces, leading to density of states and effective mass changes. We have used two different techniques to probe such changes with both the in-plane field and carrier density being systematically altered. The first technique uses a fixed perpendicular field to form Landau levels. By following the evolution of these Landau levels with in-plane field, carrier densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Where independent control of both the in-plane and perpendicular field components are necessary the sample has been mounted on an in situ rotating probe. Controlled field application coupled with computational control of the sample angle to the applied field (within <0.1 • ) allows gate-sweeps at any combination of in-plane/perpendicular field (within the magnet's range) [28].…”
Section: Experimental Datamentioning
confidence: 99%
“…Where independent control of both the in-plane and perpendicular field components are necessary the sample has been mounted on an in situ rotating probe. Controlled field application coupled with computational control of the sample angle to the applied field (within <0.1 • ) allows gate-sweeps at any combination of in-plane/perpendicular field (within the magnet's range) [28].…”
Section: Experimental Datamentioning
confidence: 99%
“…First structures of this kind have been fabricated more than a decade ago. 9,10 Since then, the interlayer tunneling in such structures has been the subject of numerous experimental [9][10][11][12][13][14][15] and theoretical 13,16 -22 studies. Measurements of the tunneling current in such structures [9][10][11][12][13] revealed peaks of the tunneling conductance in conditions in which the 2D levels in the two wells are aligned, reflecting the shape of the spectral functions within each layer, in accordance with theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%
“…By applying a magnetic field parallel to the 2DEG's (B ʈ ) the relative canonical momentum (បk) of the electron gases is changed by (eB ʈ d), where d is the separation of the two 2DEG's. The anticrossing of the displaced dispersion relations then results in distorted Fermi surfaces with both effective masses 4,5 and carrier densities 1 becoming strong functions of the in-plane field. Previous authors 1 have shown that the Fermi surface distortions may be accurately modeled using a semiclassical approach and that the observed changes in the effective mass are in good agreement with theory.…”
mentioning
confidence: 99%